Home page for accesible maths 9 Workshop Solutions

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

9.5 Workshop Solutions 5

W5.1. a) The CF is the general solution to y′′+4y=0y^{\prime\prime}+4y=0, which is Acos2x+Bsin2xA\cos 2x+B\sin 2x. This is not an exceptional case so we look for a PI of the form y(x)=b2x2+b1x+b0y(x)=b_{2}x^{2}+b_{1}x+b_{0}. Then y=2b2x+b1y^{\prime}=2b_{2}x+b_{1} so y′′=2b2y^{\prime\prime}=2b_{2}, hence y′′+4y=4b2x2+4b1x+(4b0+2b2)y^{\prime\prime}+4y=4b_{2}x^{2}+4b_{1}x+(4b_{0}+2b_{2}), so for this to equal 4x2+34x^{2}+3 we need b2=1b_{2}=1, b1=0b_{1}=0 and b0=14b_{0}=\frac{1}{4}. Thus the general solution to the inhomogeneous equation is y(x)=x2+14+Acos2x+Bsin2xy(x)=x^{2}+\frac{1}{4}+A\cos 2x+B\sin 2x.

b) The homogeneous equation here is the same as in (a), but this is an exceptional case because sin2x\sin 2x is a solution to the homogeneous equation. Thus we look for a PI of the form y(x)=Hxcos2x+Kxsin2xy(x)=Hx\cos 2x+Kx\sin 2x. Then y(x)=Hcos2x+Ksin2x-2Hxsin2x+2Kxcos2xy^{\prime}(x)=H\cos 2x+K\sin 2x-2Hx\sin 2x+2Kx\cos 2x, and y′′=-4Hsin2x+4Ksin2x-4Hxcos2x-4Kxsin2xy^{\prime\prime}=-4H\sin 2x+4K\sin 2x-4Hx\cos 2x-4Kx\sin 2x. Thus y′′+4y=-4Hsin2x+4Kcos2xy^{\prime\prime}+4y=-4H\sin 2x+4K\cos 2x, so for this to equal sin2x\sin 2x we require H=-14H=-\frac{1}{4} and K=0K=0. So the PI is -14xcos2x-\frac{1}{4}x\cos 2x, so the general solution is -14xcos2x+Acos2x+Bsin2x-\frac{1}{4}x\cos 2x+A\cos 2x+B\sin 2x.

W5.2. a) The auxiliary equation here is s2-s-2=(s-2)(s+1)=0s^{2}-s-2=(s-2)(s+1)=0, so the CF is Ae2x+Be-xAe^{2x}+Be^{-x}. Since exe^{x} is not a solution of the homogeneous equation, this is not an exceptional case and so the PI has the form CexCe^{x} for some CC. Substituting into the differential equation: if y=Cexy=Ce^{x} then y′′=y=Cexy^{\prime\prime}=y^{\prime}=Ce^{x} so y′′-y-2y=-2Cexy^{\prime\prime}-y^{\prime}-2y=-2Ce^{x}, which we want to equal exe^{x}, hence C=-12C=-\frac{1}{2}. Therefore the general solution to the (inhomogeneous) equation is y(x)=y(x)= PI + CF =Ae2x+Be-x-12ex=Ae^{2x}+Be^{-x}-\frac{1}{2}e^{x}. To find the solution to the initial value problem, we first evaluate: y(0)=A+B-12=2y(0)=A+B-\frac{1}{2}=2, to obtain A+B=52A+B=\frac{5}{2}. Secondly, we have y(x)=2Ae2x-Be-2x-12exy^{\prime}(x)=2Ae^{2x}-Be^{-2x}-\frac{1}{2}e^{x} so that y(0)=2A-B-12=1y^{\prime}(0)=2A-B-\frac{1}{2}=1, whence 2A-B=322A-B=\frac{3}{2} and so, after summing the two equations together, we obtain 3A=43A=4 and therefore A=43A=\frac{4}{3}. Subtracting this from the equation A+B=52A+B=\frac{5}{2}, we obtain B=76B=\frac{7}{6}. So the particular solution is y(x)=43e2x+76e-x-12exy(x)=\frac{4}{3}e^{2x}+\frac{7}{6}e^{-x}-\frac{1}{2}e^{x}.

b) The auxiliary equation is the same as in part (a), so the CF is Ae2x+Be-xAe^{2x}+Be^{-x} as above. However, in this case the right-hand side of the differential equation is e-xe^{-x}, which is a solution to the homogeneous equation and this is therefore an exceptional case. We therefore look for a PI of the form Cxe-xCxe^{-x}. If y(x)=Cxe-xy(x)=Cxe^{-x} then y(x)=Ce-x-Cxe-xy^{\prime}(x)=Ce^{-x}-Cxe^{-x} and y′′(x)=Cxe-x-2Ce-xy^{\prime\prime}(x)=Cxe^{-x}-2Ce^{-x}. Therefore y′′-y-2y=C(x-2-1+x-2x)e-x=-3Ce-xy^{\prime\prime}-y^{\prime}-2y=C(x-2-1+x-2x)e^{-x}=-3Ce^{-x}, hence C=-13C=\frac{-1}{3}. So the general solution to the inhomogeneous equation is y(x)=Ae2x+Be-x-13xe-xy(x)=Ae^{2x}+Be^{-x}-\frac{1}{3}xe^{-x}.

To find the particular solution, we have y(0)=A+By(0)=A+B so we require A+B=2A+B=2. Furthermore, y(x)=2Ae2x-Be-x+13xe-x-13e-xy^{\prime}(x)=2Ae^{2x}-Be^{-x}+\frac{1}{3}xe^{-x}-\frac{1}{3}e^{-x}, hence y(0)=2A-B-13y^{\prime}(0)=2A-B-\frac{1}{3}. Therefore we require 2A-B-13=12A-B-\frac{1}{3}=1 and so, after substituting B=2-AB=2-A, we obtain 3A-2=433A-2=\frac{4}{3}, hence A=109A=\frac{10}{9}, B=89B=\frac{8}{9}. So the particular solution is y(x)=109e2x+89e-x-13xe-xy(x)=\frac{10}{9}e^{2x}+\frac{8}{9}e^{-x}-\frac{1}{3}xe^{-x}.

c) Here the auxiliary equation is s2-2s+1=(s-1)2s^{2}-2s+1=(s-1)^{2}, so the CF is (Ax+B)ex(Ax+B)e^{x}. This is an exceptional case, since exe^{x} is a solution to the homogeneous equation. But in fact xexxe^{x} is also a solution, so in this case we need to look for a PI of the form Cx2exCx^{2}e^{x}. If y(x)=Cx2exy(x)=Cx^{2}e^{x} then y(x)=Cx2ex+2Cxexy^{\prime}(x)=Cx^{2}e^{x}+2Cxe^{x} and y′′(x)=Cx2ex+4Cxex+2Cexy^{\prime\prime}(x)=Cx^{2}e^{x}+4Cxe^{x}+2Ce^{x}. Hence y′′-2y+y=C(x2+4x+2-2x2-4x+x2)ex=2Cexy^{\prime\prime}-2y^{\prime}+y=C(x^{2}+4x+2-2x^{2}-4x+x^{2})e^{x}=2Ce^{x}, hence C=12C=\frac{1}{2}. Thus the general solution to the differential equation is y(x)=(12x2+Ax+B)exy(x)=(\frac{1}{2}x^{2}+Ax+B)e^{x}.

To find the particular solution, we first of all have y(0)=B=2y(0)=B=2. Next, y(x)=(12x2+Ax+B)ex+(x+A)exy^{\prime}(x)=(\frac{1}{2}x^{2}+Ax+B)e^{x}+(x+A)e^{x}, so y(0)=A+By^{\prime}(0)=A+B, which we require to equal 11. Thus A=1-B=-1A=1-B=-1. So the particular solution is y(x)=(12x2-x+2)exy(x)=(\frac{1}{2}x^{2}-x+2)e^{x}.

W5.3. Here the auxiliary equation is s2-6s+9=(s-3)2s^{2}-6s+9=(s-3)^{2}, so the general solution to the equation is (Ax+B)e3x(Ax+B)e^{3x}. (See Thm. 4.45(ii) in MATH101.) Since e3xe^{3x} is a solution to the homogeneous equation, then this is an exceptional case. But in fact, xe3xxe^{3x} is also a solution to the homogeneous equation, so we can think of this as a ‘doubly exceptional’ case, meaning that we should look for a PI of the form Cx2e3xCx^{2}e^{3x}. (See 6.31 or 6.38(c) in the notes.)

If y=Cx2e3xy=Cx^{2}e^{3x}, then y=C(2xe3x+3x2e3x)y^{\prime}=C(2xe^{3x}+3x^{2}e^{3x}) and y′′=C(2e3x+12xe3x+9x2e3x)y^{\prime\prime}=C(2e^{3x}+12xe^{3x}+9x^{2}e^{3x}), so

y′′-6y+9y=Ce3x(9x2+12x+2-18x2-12x+18x2)=2Ce3x.y^{\prime\prime}-6y^{\prime}+9y=Ce^{3x}(9x^{2}+12x+2-18x^{2}-12x+18x^{2})=2Ce^% {3x}.

So we require 2C=42C=4, hence C=2C=2 and so the general solution is y=(2x2+Ax+B)e3xy=(2x^{2}+Ax+B)e^{3x}.

W5.4. a) By linearity, (f(x))=3(x2)+2(cosx){\mathcal{L}}(f(x))=3{\mathcal{L}}(x^{2})+2{\mathcal{L}}(\cos x). Inspecting the table on 6.44, we therefore have (f(x))=6s3+2ss2+1{\mathcal{L}}(f(x))=\frac{6}{s^{3}}+\frac{2s}{s^{2}+1}.

b) By linearity we have (g(x))=(e2xcos3x)+(5){\mathcal{L}}(g(x))={\mathcal{L}}(e^{2x}\cos 3x)+{\mathcal{L}}(5). By the table on 6.44 we have (e2xcos3x)=s-2(s-2)2+9=s-2s2-4s+13{\mathcal{L}}(e^{2x}\cos 3x)=\frac{s-2}{(s-2)^{2}+9}=\frac{s-2}{s^{2}-4s+13}. Thus the answer is: (g(x))=s-2s2-4s+13+5s{\mathcal{L}}(g(x))=\frac{s-2}{s^{2}-4s+13}+\frac{5}{s}.

W5.5. i) We have f(x)=e2x2+12f(x)=\frac{e^{2x}}{2}+\frac{1}{2}, so (f(x))=12(e2x)+(12)=12(s-2)+12s{\mathcal{L}}(f(x))=\frac{1}{2}{\mathcal{L}}(e^{2x})+{\mathcal{L}}(\frac{1}{2}% )=\frac{1}{2(s-2)}+\frac{1}{2s}.

ii) Taking the Laplace transform of both sides, we have:

(y)+2(y)=-y(0)+s(y)+2(y)=(s+2)(y)=12(s-2)+12s.{\mathcal{L}}(y^{\prime})+2{\mathcal{L}}(y)=-y(0)+s{\mathcal{L}}(y)+2{\mathcal% {L}}(y)=(s+2){\mathcal{L}}(y)=\frac{1}{2(s-2)}+\frac{1}{2s}.

Therefore (y)=12(s2-4)+12s(s+2){\mathcal{L}}(y)=\frac{1}{2(s^{2}-4)}+\frac{1}{2s(s+2)}. We recall that 2s2-4\frac{2}{s^{2}-4} is the Laplace transform of sinh2x\sinh 2x, so

-1(12(s2-4))=14sinh2x.{\mathcal{L}}^{-1}\left(\frac{1}{2(s^{2}-4)}\right)=\frac{1}{4}\sinh 2x.

Similarly, 1s2-1\frac{1}{s^{2}-1} is the Laplace transform of sinhx\sinh x, so by the shift formula, 1(s+1)2-1=1s(s+2)\frac{1}{(s+1)^{2}-1}=\frac{1}{s(s+2)} is the Laplace transform of e-xsinhxe^{-x}\sinh x. Thus

-1(12s(s+2))=12e-xsinhx.{\mathcal{L}}^{-1}\left(\frac{1}{2s(s+2)}\right)=\frac{1}{2}e^{-x}\sinh x.

So the solution is y=14sinh2x+12e-xsinhx=18e2x+14-38e-2xy=\frac{1}{4}\sinh 2x+\frac{1}{2}e^{-x}\sinh x=\frac{1}{8}e^{2x}+\frac{1}{4}-% \frac{3}{8}e^{-2x}.